Electrostatic anchoring precedes stable membrane attachment of SNAP25/SNAP23 to the plasma membrane - Pascal Weber; Helena Batoulis; Kerstin M Rink; Stefan Dahlhoff; Kerstin Pinkwart; Thomas H Söllner; Thorsten Lang (eLife, 2017)
The SNAREs SNAP25 and SNAP23 are proteins that are initially cytosolic after translation, but then become stably attached to the cell membrane through palmitoylation of cysteine residues. For palmitoylation to occur, membrane association is a prerequisite, but it is unclear which motif may increase the affinities of the proteins for the target membrane. In experiments with rat neuroendocrine cells, we find that a few basic amino acids in the cysteine-rich region of SNAP25 and SNAP23 are essential for plasma membrane targeting. Reconstitution of membrane-protein binding in a liposome assay shows that the mechanism involves protein electrostatics between basic amino acid residues and acidic lipids such as phosphoinositides that play a primary role in these interactions. Hence, we identify an electrostatic anchoring mechanism underlying initial plasma membrane contact by SNARE proteins, which subsequently become palmitoylated at the plasma membrane.